1997
DOI: 10.1046/j.1468-2982.1997.1706673.x
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Placebo-Controlled Trial of Lithium in Episodic Cluster Headache

Abstract: Lithium is widely used in the prophylaxis of episodic cluster headache without formal evidence of efficacy. Placebo-controlled clinical trials are not easy in conditions characterized by frequent severe pain. In this study, it was assumed that lithium would work quickly if at all, and placebo response would be zero. Strict diagnostic criteria excluded uncertain or atypical cases. Patients were male in so-far untreated episodes expected to last for at least 3 weeks more. In a double-blind, placebo-controlled co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 10 publications
2
94
0
1
Order By: Relevance
“…In a placebo-controlled trial on the suboccipital injection of steroids no placebo response was noticed, just like in five studies on the efficacy of oral drugs in prophylactic CH therapy [28]. Two studies, which described placebo rates of 14-42%, included only patients with episodic CH [29,30]. Concerning the acute treatment of CH, the response to hyperbaric normoxic placebo was just as high as to hyperbaric 100% oxygen (25% in chronic and 83% in episodic CH patients).…”
Section: Discussionmentioning
confidence: 99%
“…In a placebo-controlled trial on the suboccipital injection of steroids no placebo response was noticed, just like in five studies on the efficacy of oral drugs in prophylactic CH therapy [28]. Two studies, which described placebo rates of 14-42%, included only patients with episodic CH [29,30]. Concerning the acute treatment of CH, the response to hyperbaric normoxic placebo was just as high as to hyperbaric 100% oxygen (25% in chronic and 83% in episodic CH patients).…”
Section: Discussionmentioning
confidence: 99%
“…Only open-label studies exist for the former, and while one crossover study suggested that the latter was as effective as verapamil, 59 a subsequent placebo-controlled randomised controlled trial of lithium carbonate (modifi ed release) 800 mg daily did not demonstrate superiority over placebo. 60 Similarly, the positive results seen in open studies of sodium valproate could not be replicated in a controlled trial. 61 There is one trial that shows that melatonin 10 mg can be effective for the prevention of cluster headache.…”
Section: Preventive Treatment For Cluster Headachementioning
confidence: 99%
“…One RCT failed to show the superiority of lithium, 800 mg, over placebo in 27 ECH patients [18]. Cessation of attacks occurred in two patients in each group within 1 week of commencing treatment, and substantial improvement was noted in 43% on placebo and 62% on lithium, although this was not statistically signifi cant.…”
Section: Lithiummentioning
confidence: 99%